Development of gluten-free and gum-free rice bread: influence of ingredients, hydration and processing time on bread quality - Luciana C. González; Eunice V. Contigiani; Marcela P. Tolaba (Discover Food, 2024)
Abstract Gluten-free and gum-free breads were developed, with the focus on the impact of raw materials (rice grain or flour) and processing conditions (pre-hydration and mixing time). The evaluation of bread quality primarily involved after the measurement of specific volume (BV), alveolar area (AA), and crumb hardness both before and storage. BV varied within 1.99–2.97 ml/g for rice bread and 2.14–2.26 ml/g for flour bread, with control (containing xanthan gum) values of 2.65 and 3.11 ml/g for rice and flour bread, respectively. An increase in AA was observed (rice: 0.5–1.9 mm2 and flour: 0.76–2.0 mm2) compared to controls with gum (rice: 0.36 and flour: 1.41 mm2). Pre-hydration of ingredients and reduced mixing time improved bread quality: volume of bread from hydrated rice and 4 min of mixing time was comparable to that of gum control. Although the aging process, measured by hardness, was faster than in gum-containing bread, process conditions were identified that delayed aging. This information is essential and valuable for future research.